ACADEMIC SELF-EFFICACY AND ACADEMIC PROCRASTINATION AS CORRELATES OF SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN ANAMBRA STATE (Journal of Guidance and Counselling Studies, 2023)
This study investigated academic self-efficacy and academic procrastination as correlates of secondary school students’ academic achievement in Anambra State. Eight research questions guided the study while four null hypotheses were tested at 0.05 level of significance. This study adopted correlation survey research design. The area of the study is Anambra State Nigeria. The population of the study consisted of all the 6,396 senior secondary year two (SS2) students in the 263 public secondary schhools in Anambra State. A sample of 1,800 SS2 English language students was used in this study using multi-stage sampling technique. Self-Efficacy Scale (SES) was adopted while Tuckman Procrastination Scale (TPS) was adapted by the researcher. The academic achievement test was measured by Mathematics and English Language examination scores derived from SS 2 English Language students’ termly results for 2022/2023 academic session. The TPS was an adapted instrument and therefore subjected to face validation by three experts. The TPS questionnaire was trial-tested using 20 students from a public secondary school in Enugu State and a co-efficient of 0.83 was obtained. Pearson Product Moment was used to answer the research questions while t-test of correlational analysis was used to test the null hypotheses at 0.05 alpha level. The finding revealed that the low positive relationship between academic self-efficacy scores and secondary school students’ academic achievement in English Language and Mathematics is significant. The findings also revealed that the very low negative relationship between academic procrastination scores and secondary school students’ academic achievement in English Language and Mathematics is significant. Based on the findings, it was recommended amongst others in as much as academic procrastination did not influence students’ academic achievement, it is hoped that students practice to manage their time as precisely as possible, because good time management can be an antidote to their academic procrastination tendency.